2001
DOI: 10.1081/jlc-100103427
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Assay for the Determination of Ascorbic Acid in Honey Samples

Abstract: Determination of ascorbic acid in honey samples was performed by high performance liquid chromatography (HPLC) with UV detection at 254 nm. The separation was performed using a C-18-ODS column with a mobile phase consisting of a mixture of 15% methanol and 85% water, adjusted to pH 2.5 with metaphosphoric acid. The mobile phase was pumped at a flow rate of 0.9 mL/min. The retention time for ascorbic acid was found to be 5.1 minutes. The method is simple, fast, sensitive, and reproducible. The recovery of ascor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Figure 1A shows the chromatogram of a vitamin C standard injected into the chromatographic system with a 0.01% H 2 SO 4 mobile phase, pH = 2.5, and T = 25 °C. The retention time for vitamin C was 2.7 min, this time was lower than the one obtained in octadecyl silane column C18 (5 μm) with other mobile phases such as methanol: H 2 O (15:85% v/v) in metaphosphoric acid at pH 2.5 (5.1 min) (Castro and others 2001) and H 2 SO 4 at pH 2.2 (9 min) (Vázquez‐Oderiz and others 1994).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Figure 1A shows the chromatogram of a vitamin C standard injected into the chromatographic system with a 0.01% H 2 SO 4 mobile phase, pH = 2.5, and T = 25 °C. The retention time for vitamin C was 2.7 min, this time was lower than the one obtained in octadecyl silane column C18 (5 μm) with other mobile phases such as methanol: H 2 O (15:85% v/v) in metaphosphoric acid at pH 2.5 (5.1 min) (Castro and others 2001) and H 2 SO 4 at pH 2.2 (9 min) (Vázquez‐Oderiz and others 1994).…”
Section: Resultsmentioning
confidence: 66%
“…Recently, vitamin C has been determined by reverse phase high‐performance liquid chromatography (RP‐HPLC) in isocratic mode, with a mobile phase of methanol/water at pH 2.5. This method is fast, it does not required sample treatment and the retention time for vitamin C is about 5 min (Castro and others 2001).…”
Section: Introductionmentioning
confidence: 99%
“…According to Tauc, the dependence of the absorption coefficient α on the photon energy hυ for near-edge optical absorption in semiconductors takes the form (2):(αhυ) 1/m = k (hυ-Eg)(2)Where Eg is the optical band gap, k is a constant and m can take the values of 1/2 in the case of an allowed direct energy gap transition and 3/2 for a forbidden direct energy gap transition[30,31]. In order to determine the optical band gap of ZnO nanorods taking m = 1/2, (αhυ)2…”
mentioning
confidence: 99%
“…Consequently, the concentration data reported in the literature are spread over four orders of magnitude, going from less than 0.1 mg/kg to values very close to 3 g/kg!!! A number of research groups have reported concentrations of ascorbic acid in honey between 5.4 and 54 mg/kg (Abu-Tarboush et al 1993;Bogdanov et al 2008;Castro et al 2001;Ciulu et al 2011;Haydak et al 1942;White 1975).…”
Section: Vitamin C: Ascorbic Acidmentioning
confidence: 96%
“…In contrast, the following three research groups did not find any ascorbic acid in any honey sample. First, Castro et al (2001) added metaphosphoric acid in the mobile phase (a MeOH/H 2 O solution, 15/85 v/v) while using a C18-ODS column. The revelation was accomplished at 254 nm.…”
Section: Assay Of Vitamin C In Honeymentioning
confidence: 99%